'Remixing Rasmussen': The evolution of Accimaps within systemic accident analysis. (March 2017) - Waterson, Patrick; Jenkins, Daniel P.; Salmon, Paul M.; Underwood, Peter
Abstract: Throughout Jens Rasmussen's career there has been a continued emphasis on the development of methods, techniques and tools for accident analysis and investigation. In this paper we focus on the evolution and development of one specific example, namely Accimaps and their use for accident analysis. We describe the origins of Accimaps followed by a review of 27 studies which have applied and adapted Accimaps over the period 2000–2015 to a range of domains and types of accident. Aside from demonstrating the versatility and popularity of the method, part of the motivation for the review of the use of Accimaps is to address the question of what constitutes a sound, usable, valid and reliable approach to systemic accident analysis. The findings from the review demonstrate continuity with the work carried out by Rasmussen, as well as significant variation (e.g., changes to the Accimap, used of additional theoretical and practice-oriented perspectives on safety). We conclude the paper with some speculations regarding future extension and adaptation of the Accimap approach including the possibility of using hybrid models for accident analysis. Highlights: The paper provides a review of the use of Accimaps for systems and accident analysis. 27 studies covering a range of domains including transportation, nuclear and public safety were reviewed. The outcomes from the review highlight theoretical and practical aspects of Rasmussen's work over the course of his career.